Boosting Electrochemical Urea Synthesis via Constructing Ordered Pd–Zn Active Pair - Zhou, Weiliang; Feng, Chao; Li, Xuan; Jiang, Xingxing; Jing, Lingyan; Qi, Shuai; Huo, Qihua; Lv, Miaoyuan; Chen, Xinbao; Huang, Tianchi; Zhao, Jingwen; Meng, Na; et al. (Nano-Micro Letters, 2024)
Electrochemical co-reduction of nitrate (NO3–) and carbon dioxide (CO2) has been widely regarded as a promising route to produce urea under ambient conditions, however the yield rate of urea has remained limited. Here, we report an atomically ordered intermetallic pallium-zinc (PdZn) electrocatalyst comprising a high density of PdZn pairs for boosting urea electrosynthesis. It is found that Pd and Zn are responsible for the adsorption and activation of NO3– and CO2, respectively, and thus the co-adsorption and co-activation NO3– and CO2 are achieved in ordered PdZn pairs. More importantly, the ordered and well-defined PdZn pairs provide a dual-site geometric structure conducive to the key C–N coupling with a low kinetical barrier, as demonstrated on both operando measurements and theoretical calculations. Consequently, the PdZn electrocatalyst displays excellent performance for the co-reduction to generate urea with a maximum urea Faradaic efficiency of 62.78% and a urea yield rate of 1274.42 μg mg–1 h–1, and the latter is 1.5-fold larger than disordered pairs in PdZn alloys. This work paves new pathways to boost urea electrosynthesis via constructing ordered dual-metal pairs. Highlights: 1 Ordered intermetallic pallium-zinc (PdZn) electrocatalyst comprising a high density of PdZn pairs is synthesized for achieving co-adsorption and co-activation carbon dioxide and nitrate. 2 Both operando measurements and theoretical calculations reveal that the PdZn pairs provide a dual-site geometric structure conducive to the key C–N coupling with a low kinetical barrier. 3 The intermetallic PdZn displays excellent performance for the co-reduction of nitrate (NO3–) and carbon dioxide (CO2) toward urea, with a maximum FEurea of 62.78% at a small potential of – 0.4 V versus RHE.